Strategi Humas dalam Membangun Kepercayaan Publik terhadap Mutu Pendidikan di Sekolah - Rizka Amalia; Sudadi Sudadi (JURNAL MAPPESONA, 2025)
Public trust in the quality of education in schools is an important factor in improving the image and reputation of educational institutions. This study aims to analyze public relations strategies in building public trust in the quality of education in schools. The research method used is library research, by reviewing various relevant literature, scientific journals and previous research in the last five years. The results show that an effective PR strategy involves transparent communication, utilization of digital media, stakeholder involvement, and responsive crisis management. The findings also confirm that public trust can be strengthened through consistent delivery of accurate information, creation of a positive image, and collaboration with various parties, including parents and the surrounding community. The implication of this study is the importance of schools adopting more adaptive and technology-based communication strategies to build strong relationships with the public.